Distribuição geográfica do htlv-1/2 em mães de recém-nascidos submetidos à triagem neonatal em Minas Gerais, Brasil - Maisa Aparecida Ribeiro (2009)
BACKGROUND: The Human T-cell lymphotropic virus (HTLV-1 and HTLV-2) are human retrovirus with tropism for T lymphocytes. The HTLV-1 is distributed worldwide and is endemic in various parts of the world, including Brazil. Studies have shown a tendency to grouping of seropositive individuals in different geographical areas of the world. The viral transmission from mother to child, which occurs mainly through breastfeeding, is a major factor maintaining the chain of transmission of these viruses. Reported rates of vertical transmission range from 15 to 25%. The presence of specific antibodies anti-HTLV-1/2 in neonates is considered a reliable marker of maternal infection. Approximately 1 to 5% of children infected through vertical to develop leukemia/lymphoma adult T-cell. The present cross sectional observational study evaluated the distribution of HTLV-1/2 for puerperal women of Minas Gerais who had their newborn submitted to HTLV-1/2 neonatal screening. The relationship between seropositivity and determinants of socioeconomic position was also examined. METHODS: Minas Gerais State is located in Southeast Brazil, has 586,528.293 Km2 area and 19,273,506 inhabitants. The units of analysis used were Minas Gerais State geographic areas (n=12). Samples consisting of dried blood spots (DBS) were collected from newborns on filter papers, from September to November 2007. These were tested for IgG maternal anti-HTLV-1/2, by enzyme immunoassay (EIA) (Prime Diagnostic do Brasil, São Paulo), specific for detection of anti-HTLV-1 and/or HTLV-2 in samples of dried bloodcollected on filter paper. The mothers, whose newborns were reactive in DBS, had their venous blood collected and the serum was submitted to EIA (Ortho Clinical Diagnostic Inc, USA). The samples found positive were tested with Western Blot (MP Diagnostics, Singapore), as a confirmatory test. RESULTS: Of the 55,293 samples on filter paperincluded in the analysis, 52 were reactive (9.4/10,000, 95% CI: 6.8 to 12.0). HTLV-1/2 positivity was confirmed by WB in 42 mothers (7.6/10,000, 95% CI: 5.3 to 9.9). Two have been identified as carriers of the HTLV-2 and all the remaining were positive to HTLV-1. In only two Minas Gerais geographic areas, Campo das Vertentes and Central Mineira, no samples tested were reactive to HTLV-1/2. In others areas, the seropositivity for HTLV-1/2 ranged from 1.4 to 55.9/10,000. The highest rates of seropositivity were observed in the Vale do Mucuri (55.9/10,000) and Jequitinhonha (16.0/10,000). DISCUSSION: The HTLV-1/2 geographical distribution was heterogeneous, but with a tendency to concentrate in the Northern and Northeastern parts of the state. Regions with the highest rates of seropositivitycoincided with those that have, on average, the worst indicators of socioeconomic position inthe State. Knowledge of areas with higher prevalence of HTLV-1/2 in pregnant women may allow the planning of public health interventions, such as screening in prenatal or neonatal periods. These actions, together with measures of intervention, such as supplying formulamilk for newborns of HTLV positive mothers, may drastically reduce the vertical transmission of the virus.